example: (p ∨ q) ∧ (p ∨ r) → p ∨ (q ∧ r)
问题 Section 3.6 of Theorem Proving in Lean shows the following: example : p ∨ (q ∧ r) ↔ (p ∨ q) ∧ (p ∨ r) := sorry Since this involves iff , let's demonstrate one direction first, left to right: example : p ∨ (q ∧ r) → (p ∨ q) ∧ (p ∨ r) := (assume h : p ∨ (q ∧ r), or.elim h (assume hp : p, show (p ∨ q) ∧ (p ∨ r), from ⟨or.inl hp, or.inl hp⟩) (assume hqr : q ∧ r, have hq : q, from hqr.left, have hr : r, from hqr.right, show (p ∨ q) ∧ (p ∨ r), from ⟨or.inr hq, or.inr hr⟩)) To go the other direction